Large-size highly-homogenized infrared chalcogenide glass as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411968484.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-30
AI Technical Summary
During the preparation process of existing large-size infrared sulfur glass, the raw materials have poor purification effect and many residues, and the synthesis process is prone to stripes and cracks, affecting optical uniformity and internal quality.
The raw material purification is carried out by low-temperature reduction method or low-temperature solid fractionation method, combined with high-temperature sway melting and supercooling curing processes, and two annealing processes combined with special molds are used for precision annealing.
The high uniformity, stripes, stable transmission performance and low stress of large-size infrared sulfur glass are achieved, and the quality and performance stability of the glass are improved.
Smart Images

Figure CN119638193A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of infrared optical material preparation, and in particular to a large-size highly uniform infrared chalcogenide glass and a preparation method and application thereof. Background Art
[0002] Infrared chalcogenide glass is a type of amorphous infrared optical material based on sulfur (S), selenium (Se), and tellurium (Te) in Group VI of the periodic table, with the introduction of other metal or non-metal elements (Ge, As, Sb, etc.). Compared with single crystal or polycrystalline infrared materials, infrared chalcogenide glass has excellent infrared transmittance, low refractive index temperature coefficient, excellent athermalization and other properties. It is an ideal material for thermal and chromatic aberration correction of infrared optical systems. It is regarded as a must-have material for the new generation of infrared thermal imaging systems to achieve passive athermal design, temperature self-adaptation and other functions. High-quality infrared chalcogenide glass needs to meet the requirements of high transmittance, low absorption, low impurity content, no streak defects, no cracks, and optical uniformity better than 2×10 -4 Requirements such as these are the key to realizing the design of key equipment models and their engineering.
[0003] The preparation process of infrared chalcogenide glass mainly includes four stages: raw material purification, material preparation, synthesis and annealing heat treatment. Among them, the distillation purification method commonly used for raw material purification can meet the requirements of low absorption and low impurity content of small-weight infrared chalcogenide glass, but it is difficult to meet the precision requirements of large-size ingots, and it is easy to have problems such as low distillation efficiency, high impurity residues and inconsistent loss ratios. The synthesis process determines the quality state of the infrared chalcogenide glass blank, which in turn affects the effect of the annealing heat treatment process in reducing material stress. The synthesis process of infrared chalcogenide glass mostly adopts a combination of high-temperature swing melting, cooling and quenching operations. Among them, the quenching process refers to cooling the temperature to 200-600°C, taking out the quartz bottle containing the melt for rapid cooling, but there are the following problems in the rapid cooling process: infrared chalcogenide glass has poor thermal conductivity, extremely short rapid cooling time, increased instantaneous temperature gradient, inconsistent flow ability, easy to cause defects, and seriously affect the internal quality and optical uniformity of the glass; especially when preparing large-size chalcogenide glass, the radial size of the infrared chalcogenide glass blank increases, the disadvantage of poor thermal conductivity is further highlighted, the temperature gradient and viscosity gradient are further increased, the difficulty of controlling the melt to not flow is further increased, defects such as cracks and streaks are difficult to control, and disadvantages such as optical unevenness are further highlighted.
[0004] Therefore, the development of a large-size infrared chalcogenide glass that is free of streaks, has stable transmittance, high optical uniformity and low stress is of great significance for the research of infrared optical materials. Summary of the invention
[0005] In view of the problems that the raw material purification effect is poor and there are many residues in the existing large-size infrared chalcogenide glass preparation process, and stripes and cracks are easily generated in the synthesis process, which affects the optical uniformity and internal quality of the infrared chalcogenide glass, the present invention provides a large-size highly uniform infrared chalcogenide glass and its preparation method and application.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a large-sized and highly uniform infrared chalcogenide glass, comprising the following steps: Step 1: purifying the raw materials by a low-temperature reduction method or a low-temperature solid fractionation method, mixing, and obtaining a purified mixture; the raw materials include at least two of Ge, As, Sb, Se, or Te; Step 2: Put the purified mixture into a quartz tube, vacuum dry it, seal the tube mouth with vacuum, and perform high-temperature swing melting at 750°C-900°C. After cooling to 300°C-600°C, place the quartz tube in a supercooled atmosphere and let it stand for solidification to obtain a glass precursor material. Step 3: heating the glass precursor material to 20°C-40°C below the glass transition temperature for the first annealing treatment, keeping the temperature, and removing the quartz tube outside the glass precursor material after cooling to room temperature to obtain a glass blank; Step 4: placing the glass blank in a mold for precision annealing treatment and slowly cooling to obtain a large-sized and highly uniform infrared chalcogenide glass; In step 4, the mold includes a ring, an upper cover plate and a lower base plate. When the ratio of the diameter of the glass blank to the thickness of the glass blank is ≥3, the thermal conductivity of the material used for the ring is 0.1Wm -1 K -1 -0.3Wm -1 K -1 When the ratio of the diameter of the glass blank to the thickness of the glass blank is less than 3, the thermal conductivity of the material used for the ring is 100Wm -1 K -1 -150Wm -1 K -1 The thermal conductivity of the material used for the upper cover plate and the lower base plate is 100Wm -1 K -1 -150Wm -1 K -1 .
[0007] Compared with the prior art, the present invention adopts a low-temperature reduction method or a low-temperature solid fractionation method to first purify the raw materials, so as to remove the oxide layer on the surface of the raw materials, reduce the impurity content, ensure the purity consistency and stability of the raw materials when feeding, and improve the purity of the glass. The low-temperature reduction method or the low-temperature solid fractionation method can meet the precision requirements of large-size ingots, is not easy to produce impurity residues, and has high extraction efficiency. The present invention also performs supercooling solidification on the materials after high-temperature swing melting. Compared with water-cooling solidification or air-cooling solidification, the process of static solidification in a supercooled atmosphere is more gentle, and can also effectively solve the problem of stripe defects that occur during solidification and molding, thereby avoiding the problem of poor internal quality of the glass material and improving the quality of infrared chalcogenide glass.
[0008] In the annealing heat treatment, the present invention creatively proposes a two-time annealing process combined with a special mold to anneal and eliminate the stress of the glass material, which significantly reduces the residual stress inside the obtained infrared chalcogenide glass, improves the optical uniformity of the large-size infrared chalcogenide glass, and makes its performance more stable and reliable. More importantly, the present invention uses a special mold for precision annealing. According to the size of the sample, materials with different thermal conductivities are used as the mold ring. For samples with smaller sizes, materials with high thermal conductivity are selected as the mold ring, which can effectively avoid the rapid heat transfer during cooling, resulting in a large temperature gradient on the surface and inside of the material, and generate new stress. When the ratio of the sample diameter to the thickness of the glass blank is large, a material with low thermal conductivity is used as the mold ring, which can effectively control the temperature gradient during precision annealing, the temperature difference between the inside and outside is small, and the thermal stress is relatively unobvious, which helps to reduce the internal structural defects caused by temperature differences, so that the glass material can be cooled and cooled more evenly, thereby effectively eliminating residual stress and improving optical uniformity.
[0009] In summary, the method for preparing a large-sized, highly uniform infrared chalcogenide glass provided by the present invention can produce a large-sized, stripe-free, optically uniform, stable transmittance and low-stress chalcogenide glass product, which effectively solves the problems of poor raw material purification and high residue in the existing large-sized infrared chalcogenide glass preparation process, and the easy occurrence of stripes and cracks in the synthesis process, which affects the optical uniformity and internal quality of the infrared chalcogenide glass, and provides a new idea for the research and development of large-sized infrared chalcogenide glass.
[0010] Preferably, in step 1, the Ge single substance is purified by a low-temperature reduction method for Ge particles, the reduction temperature is 700° C.-750° C., and the reduction time is 2 h-4 h.
[0011] Preferably, in step 1, the As single substance is purified by low-temperature solid fractionation of As particles, the fractionation temperature is 200° C.-240° C., and the fractionation time is 1 h-3 h.
[0012] Preferably, in step 1, the purity of each component in the purified mixture is ≥ 99.9999%.
[0013] Preferably, in step 2, the vacuum drying temperature is 65°C-85°C, the vacuum drying time is 60min-80min, and the vacuum degree of vacuum drying is less than 1×10 -3 Pa.
[0014] Preferably, in step 2, the specific operation of the high-temperature swing melting is: transfer the quartz tube with the tube mouth sealed to a swing furnace, heat it to 750°C-900°C at a heating rate of 1°C / min-4°C / min, and then perform asymmetrical swinging after constant temperature, and keep it warm for 8h-20h.
[0015] Further preferably, the inclination angle of the asymmetric swing is -40°-40°, and the swing frequency is 5 times / min-15 times / min.
[0016] Preferably, in step 2, the temperature of the supercooled atmosphere is 60°C-240°C.
[0017] Preferably, in step 2, the static curing time is 1h-3h.
[0018] Preferably, in step three, the holding time of the first annealing treatment is 4h-6h.
[0019] Preferably, in step three, programmed cooling is used to lower the temperature to room temperature, with a cooling rate of 0.2°C / min-0.5°C / min.
[0020] Preferably, in step 4, the temperature of the precision annealing treatment is 170°C-400°C, and the holding time of the precision annealing treatment is 10h-50h.
[0021] Preferably, in step 4, slow cooling is performed by programmed cooling, with a cooling rate of 0.02°C / min-0.1°C / min.
[0022] Preferably, in step 4, the distance between the edge of the mold and the edge of the glass blank is 2 mm-5 mm.
[0023] A second aspect of the present invention provides a large-sized highly uniform infrared chalcogenide glass, which is prepared by using the preparation method of the large-sized highly uniform infrared chalcogenide glass.
[0024] A third aspect of the present invention provides an application of a large-sized and highly uniform infrared chalcogenide glass in the preparation of infrared optical materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a process flow chart of each embodiment and comparative example; Figure 2 It is a schematic diagram of the structure of the mold used in each embodiment and comparative example; Figure 3 is the transmittance spectrum of Example 1; Figure 4 The radial stress distribution diagram of the large-sized and highly uniform infrared chalcogenide glass obtained in Example 1 and Comparative Examples 3-4; Figure 5 Graph showing radial stress distribution of large-sized, highly uniform infrared chalcogenide glasses obtained in Example 1 and Comparative Example 5. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 This embodiment provides a large-sized and highly uniform infrared chalcogenide glass As 40 Se 60 The preparation method specifically comprises the following steps: Step 1: put arsenic particles with a purity of 99.9999% into a quartz boat, place the quartz boat in a quartz tube, connect the quartz tube to a vacuum deoxidation device, perform a "vacuum-fill with protective gas-vacuum" cycle for 4 times, fully exhaust the air in the quartz tube, heat to 220°C, keep warm for 2 hours, then cool to room temperature, flush with protective gas to normal pressure, remove the quartz tube in an oxygen-free protective atmosphere, take out the quartz boat and transfer it to an oxygen-free glove box; obtain high-purity As particles; according to Ф130×50mm, weigh 1190.58g of high-purity As particles and 1882.16g of selenium particles in proportion in an oxygen-free glove box, and put them into a quartz tube with a diameter of Ф130mm, wherein the purity of the selenium particles is 99.9999%; Step 2: Connect the quartz tube to a vacuum pump and evacuate to a vacuum of <1×10 -3 Pa, then keep the temperature at 70°C for 1 hour, seal the tube mouth of the quartz container with a hydrogen-oxygen flame, transfer to a synthesis furnace, heat to 800°C at a heating rate of 2°C / min, and then perform asymmetric shaking after constant temperature to mix evenly, and keep the temperature for 12 hours; cool to 450°C, take out the quartz tube, place it in a supercooling range of 60°C for 2 hours for supercooling solidification, and obtain a glass precursor material; Step 3: heating the glass precursor material to 155° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it down to room temperature at a cooling rate of 0.3° C. / min, and then removing the quartz tube outside the glass precursor material to obtain a cylindrical glass blank with a diameter of 130×40 mm and a flat top and bottom surface; Step 4: Place the cylindrical glass blank in a large diameter mold, then place the large diameter mold in a precision annealing furnace and heat it to 180°C for precision annealing, keep it warm for 30 hours, and slowly cool it to room temperature at a cooling rate of 0.06°C / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0028] The internal dimensions of the large-diameter mold are 130×45 mm, including a ring, an upper cover plate, and a lower bottom plate. The ring is made of polycrystalline alumina composite fiberboard with a thermal conductivity of 0.2 Wm -1 K -1 ; The upper cover and lower base are both made of graphite, with a thermal conductivity of 130Wm -1 K -1 .
[0029] Example 2 This embodiment provides a large-sized, highly uniform infrared chalcogenide glass Ge 10 As 40 Se 50 The preparation method specifically comprises the following steps: Step 1: Put 99.9999% pure arsenic raw material into a quartz boat, place the quartz boat in a quartz tube, connect the quartz tube to a vacuum deoxidation device, perform a "vacuum-fill with protective gas-vacuum" cycle for 4 times, fully exhaust the air in the quartz tube, heat to 220°C, keep warm for 2 hours, then cool to room temperature, flush with protective gas to normal pressure, remove the quartz tube in an oxygen-free protective atmosphere, take out the quartz boat and transfer it to an oxygen-free glove box; obtain high-purity As particles; Put the zone melting germanium ingot into a high-purity quartz boat, place it in a hydrogen reduction furnace, exhaust the air, introduce argon protection, heat it to 740°C, then introduce hydrogen and argon mixed gas, reduce it for 2 hours, then cool it to room temperature, stop introducing hydrogen and continue introducing argon, take out the germanium ingot in an oxygen-free environment after 15 minutes, and transfer it into an oxygen-free glove box to obtain a high-purity germanium ingot; According to Ф180×50mm, 2236.72g of high-purity As particles, 542.16g of high-purity germanium ingots and 2946.67g of selenium particles were weighed in proportion in an oxygen-free glove box and loaded into a quartz tube with a diameter of Ф180mm. The purity of the selenium particles was 99.9999%; Step 2: Connect the quartz tube to a vacuum pump and evacuate to a vacuum of <1×10 -3 Pa, then keep the temperature at 70°C for 1 hour, seal the tube mouth of the quartz container with a hydrogen-oxygen flame, transfer to a synthesis furnace, heat to 880°C at a heating rate of 1.5°C / min, and then perform asymmetric shaking after constant temperature to mix evenly, and keep the temperature for 12 hours; cool to 500°C, take out the quartz tube, place it in a supercooling range of 90°C for 2 hours for supercooling solidification, and obtain a glass precursor material; Step 3: heating the glass precursor material to 194° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it down to room temperature at a cooling rate of 0.3° C. / min, and then removing the quartz tube outside the glass precursor material to obtain a cylindrical glass blank with a diameter of 180×40 mm and a flat top and bottom surface; Step 4: Place the cylindrical glass blank in a large diameter mold, then place the large diameter mold in a precision annealing furnace and heat it to 230°C for precision annealing, keep it warm for 40 hours, and slowly cool it to room temperature at a cooling rate of 0.06°C / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0030] The internal dimensions of the large-diameter mold are 180×45 mm, including a ring, an upper cover plate, and a lower bottom plate. The ring is made of polycrystalline alumina composite fiberboard with a thermal conductivity of 0.2 Wm -1 K -1 ; The upper cover and lower base are made of graphite, with a thermal conductivity of 130Wm -1 K -1 .
[0031] Example 3 This embodiment provides a large-sized, highly uniform infrared chalcogenide glass Ge 28 Sb 12 Se 60 The preparation method specifically comprises the following steps: Step 1: Place the zone melting germanium ingot in a high-purity quartz boat, place it in a hydrogen reduction furnace, exhaust the air, introduce argon protection, heat it to 740°C, then introduce a hydrogen-argon mixed gas, reduce it for 2 hours, then cool it to room temperature, stop introducing hydrogen and continue introducing argon, take out the germanium ingot after 15 minutes without oxygen, and transfer it to an oxygen-free glove box to obtain a high-purity germanium ingot; According to the calculation of Ф120×40mm, 652.47g high-purity germanium ingot, 468.73g antimony granules and 1519.62g selenium granules were weighed in proportion in an oxygen-free glove box and loaded into a quartz tube with a diameter of Ф120mm. The purity of the antimony granules and selenium granules were both 99.9999%; Step 2: Connect the quartz tube to a vacuum pump and evacuate to a vacuum of <1×10 -3 Pa, then keep the temperature at 70°C for 1 hour, seal the tube mouth of the quartz container with a hydrogen-oxygen flame, transfer to a synthesis furnace, heat to 880°C at a heating rate of 2°C / min, perform asymmetric shaking after constant temperature, mix evenly, and keep the temperature for 12 hours; cool to 540°C, take out the quartz tube, place it in a supercooling range of 120°C and stand for 2 hours for supercooling solidification to obtain a glass precursor material; Step 3: heating the glass precursor material to 250° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it to room temperature at a cooling rate of 0.3° C. / min, removing the quartz tube outside the glass precursor material, and obtaining a cylindrical glass blank with a diameter of 120×40 mm and a flat upper and lower surface; Step 4: Place the cylindrical glass blank in a large diameter mold, then place the large diameter mold in a precision annealing furnace and heat it to 180°C for precision annealing, keep it warm for 30 hours, and slowly cool it to room temperature at a cooling rate of 0.06°C / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0032] The internal dimensions of the large-diameter mold are 124×45 mm, including a ring, an upper cover plate, and a lower bottom plate. The ring is made of polycrystalline alumina composite fiberboard with a thermal conductivity of 0.2 Wm -1 K -1 ; The upper cover and lower base are made of graphite, with a thermal conductivity of 130Wm -1 K -1 .
[0033] Comparative Example 1 This comparative example provides a large-sized, highly uniform infrared chalcogenide glass As 40 Se 60 The preparation method of Example 1 is different from that of Example 1 in that the arsenic raw material is purified by distillation, and other processes and parameters remain unchanged, and specifically comprises the following steps: Step 1: According to the calculation of 130×50mm, weigh 1190.58g arsenic particles and 1882.16g selenium in proportion in an oxygen-free glove box, put them into a double-zone "H" type quartz tube, and evacuate to <1×10 -3 Pa, then keep warm at 70℃ for 1h, seal the tube mouth of the quartz container with oxyhydrogen flame, put the sealed tube into a double-temperature zone distillation furnace, the temperature of the quartz reactor end for collecting the purified material is 200℃, and the temperature of the loading quartz tube end is 900℃, and distillation and purification are carried out; wherein, the purity of arsenic particles is 99.9999%, and the purity of selenium is 99.9999%; purified arsenic and selenium are obtained at the quartz reactor end, and the double tubes are sealed with oxyhydrogen flame.
[0034] Step 2: Transfer the sealed quartz reactor containing purified arsenic and selenium to a synthesis furnace, heat it to 800°C at a heating rate of 2°C / min, and then shake it asymmetrically to mix it evenly, and keep it warm for 12 hours; cool it to 450°C, take out the quartz tube, and place it in a supercooling range of 60°C for 2 hours for supercooling solidification to obtain a glass precursor material; Step 3: heating the glass precursor material to 155° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it down to room temperature at a cooling rate of 0.3° C. / min, and then removing the quartz tube outside the glass precursor material to obtain a cylindrical glass blank with a diameter of 130×40 mm and a flat top and bottom surface; Step 4: Place the cylindrical glass blank in a large diameter mold, then place the large diameter mold in a precision annealing furnace and heat it to 180°C for precision annealing, keep it warm for 30 hours, and slowly cool it to room temperature at a cooling rate of 0.06°C / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0035] The internal dimensions of the large-diameter mold are 130×45 mm, including a ring, an upper cover plate, and a lower bottom plate. The ring is made of polycrystalline alumina composite fiberboard with a thermal conductivity of 0.2 Wm -1 K -1 ; The upper cover and lower base are both made of graphite, with a thermal conductivity of 130Wm -1 K -1 .
[0036] Comparative Example 2 This comparative example provides a large-sized, highly uniform infrared chalcogenide glass As 40 Se 60 The preparation method of the embodiment 1 is different from that of the embodiment 1 in that water cooling is used instead of curing in a supercooled atmosphere, and other processes and parameters remain unchanged, and specifically comprises the following steps: Step 1: put arsenic particles with a purity of 99.9999% into a quartz boat, place the quartz boat in a quartz tube, connect the quartz tube to a vacuum deoxidation device, perform a "vacuum-fill with protective gas-vacuum" cycle for 4 times, fully exhaust the air in the quartz tube, heat to 220°C, keep warm for 2 hours, then cool to room temperature, flush with protective gas to normal pressure, remove the quartz tube in an oxygen-free protective atmosphere, take out the quartz boat and transfer it to an oxygen-free glove box; obtain high-purity As particles; according to Ф130×50mm, weigh 1190.58g of arsenic particles and 1882.16g of selenium particles in proportion in an oxygen-free glove box, and put them into a quartz tube with a diameter of Ф130mm, wherein the purity of the selenium particles is 99.9999%; Step 2: Connect the quartz tube to a vacuum pump and evacuate to a vacuum of <1×10 -3 Pa, then keep the temperature at 70°C for 1 hour, seal the tube mouth of the quartz container with a hydrogen-oxygen flame, transfer it to a synthesis furnace, heat it to 800°C at a heating rate of 2°C / min, and then perform asymmetric shaking after constant temperature to mix evenly, and keep the temperature for 12 hours; cool it to 450°C, take out the quartz tube, spray water on the quartz tube, make it cool and solidify quickly, and obtain a glass precursor material; Step 3: heating the glass precursor material to 155° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it down to room temperature at a cooling rate of 0.3° C. / min, and then removing the quartz tube outside the glass precursor material to obtain a cylindrical glass blank with a diameter of 130×40 mm and a flat top and bottom surface; Step 4: Place the cylindrical glass blank in a large diameter mold, then place the large diameter mold in a precision annealing furnace and heat it to 180°C for precision annealing, keep it warm for 30 hours, and slowly cool it to room temperature at a cooling rate of 0.06°C / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0037] The internal dimensions of the large-diameter mold are 130×45 mm, including a ring, an upper cover plate, and a lower bottom plate. The ring is made of polycrystalline alumina composite fiberboard with a thermal conductivity of 0.2 Wm -1 K -1 ; The upper cover and lower base are both made of graphite, with a thermal conductivity of 130Wm -1 K -1 .
[0038] Comparative Example 3 This comparative example provides a large-sized, highly uniform infrared chalcogenide glass As 40 Se 60 The preparation method of the embodiment 1 is different from that of the embodiment 1 in that air cooling is used instead of curing in a supercooled atmosphere, and other processes and parameters remain unchanged, and specifically comprises the following steps: Step 1: put arsenic particles with a purity of 99.9999% into a quartz boat, place the quartz boat in a quartz tube, connect the quartz tube to a vacuum deoxidation device, perform a "vacuum-fill with protective gas-vacuum" cycle for 4 times, fully exhaust the air in the quartz tube, heat to 220°C, keep warm for 2 hours, then cool to room temperature, flush with protective gas to normal pressure, remove the quartz tube in an oxygen-free protective atmosphere, take out the quartz boat and transfer it to an oxygen-free glove box; obtain high-purity As particles; according to Ф130×50mm, weigh 1190.58g of arsenic particles and 1882.16g of selenium particles in proportion in an oxygen-free glove box, and put them into a quartz tube with a diameter of Ф130mm, wherein the purity of the selenium particles is 99.9999%; Step 2: Connect the quartz tube to a vacuum pump and evacuate to a vacuum of <1×10 -3 Pa, then keep the temperature at 70°C for 1 hour, seal the tube mouth of the quartz container with a hydrogen-oxygen flame, transfer to a synthesis furnace, heat to 800°C at a heating rate of 2°C / min, and then perform asymmetric shaking after constant temperature to mix evenly, and keep the temperature for 12 hours; cool to 450°C, take out the quartz tube, send the quartz tube to a cooling furnace, ventilate for cooling and solidification, and the ventilation volume is 1NL / min to obtain a glass precursor material; Step 3: heating the glass precursor material to 155° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it down to room temperature at a cooling rate of 0.3° C. / min, and then removing the quartz tube outside the glass precursor material to obtain a cylindrical glass blank with a diameter of 130×40 mm and a flat top and bottom surface; Step 4: Place the cylindrical glass blank in a large diameter mold, then place the large diameter mold in a precision annealing furnace and heat it to 180°C for precision annealing, keep it warm for 30 hours, and slowly cool it to room temperature at a cooling rate of 0.06°C / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0039] The internal dimensions of the large-diameter mold are 130×45 mm, including a ring, an upper cover plate, and a lower bottom plate. The ring is made of polycrystalline alumina composite fiberboard with a thermal conductivity of 0.2 Wm -1 K -1 ; The upper cover and lower base are both made of graphite, with a thermal conductivity of 130Wm -1 K -1 .
[0040] Comparative Example 4 This comparative example provides a large-sized, highly uniform infrared chalcogenide glass As 40 Se 60 The preparation method of the embodiment 1 is different from that of the embodiment 1 in that the precision annealing is performed in a moldless manner, and other processes and parameters remain unchanged, and specifically comprises the following steps: Step 1: put arsenic particles with a purity of 99.9999% into a quartz boat, place the quartz boat in a quartz tube, connect the quartz tube to a vacuum deoxidation device, perform a "vacuum-fill with protective gas-vacuum" cycle for 4 times, fully exhaust the air in the quartz tube, heat to 220°C, keep warm for 2 hours, then cool to room temperature, flush with protective gas to normal pressure, remove the quartz tube in an oxygen-free protective atmosphere, take out the quartz boat and transfer it to an oxygen-free glove box; obtain high-purity As particles; according to Ф130×50mm, weigh 1190.58g of arsenic particles and 1882.16g of selenium particles in proportion in an oxygen-free glove box, and put them into a quartz tube with a diameter of Ф130mm, wherein the purity of the selenium particles is 99.9999%; Step 2: Connect the quartz tube to a vacuum pump and evacuate to a vacuum of <1×10 -3 Pa, then keep the temperature at 70°C for 1 hour, seal the tube mouth of the quartz container with a hydrogen-oxygen flame, transfer to a synthesis furnace, heat to 800°C at a heating rate of 2°C / min, and then perform asymmetric shaking after constant temperature to mix evenly, and keep the temperature for 12 hours; cool to 450°C, take out the quartz tube, place it in a supercooling range of 60°C for 2 hours for supercooling solidification, and obtain a glass precursor material; Step 3: heating the glass precursor material to 155° C. for the first annealing treatment, keeping the temperature for 5 hours, and then cooling it down to room temperature at a cooling rate of 0.3° C. / min, and then removing the quartz tube outside the glass precursor material to obtain a cylindrical glass blank with a diameter of 130×40 mm and a flat top and bottom surface; Step 4: Place the cylindrical glass blank in a precision annealing furnace and heat it to 180° C. for precision annealing treatment, keep it warm for 30 hours, and slowly cool it to room temperature at a cooling rate of 0.06° C. / min to obtain a large-sized, highly uniform infrared chalcogenide glass.
[0041] In order to further reflect the technical effect of the present invention, the large-size and highly uniform infrared chalcogenide glasses obtained in Examples 1-3 and Comparative Examples 1-4 of the present invention were subjected to the following tests: stress tests were performed on the samples obtained in each Example and Comparative Example with reference to the national standard GB / T32561.5-2022; striation tests were performed on the samples obtained in each Example and Comparative Example with reference to the national standard GB / T32561.2-2016; uniformity tests were performed on the samples obtained in each Example and Comparative Example with reference to the national standard GB / T36265-2018; refractive index tests were performed on the samples obtained in each Example and Comparative Example with reference to the national standard GB / T34184-2017; bending strength tests were performed on the samples obtained in each Example and Comparative Example with reference to the national standard GB / T6569-2006; hardness tests were performed on the samples obtained in each Example and Comparative Example with reference to the national standard GB / 16534-2009; the test results are shown in Tables 1 and Figure 3-5 shown.
[0042] Table 1 Performance test results of samples obtained from various embodiments and comparative examples
[0043] According to Table 1 and Figure 3-5 It can be seen that the transmittance of the sample obtained in Example 1 in the 2μm-16μm band is ≥50%, and the absorption of -OH, HOH, As-O, Se-O, etc. is significantly reduced; the change amplitude of the stress of the 20mm thick sample after curing in Example 1 is significantly reduced; after precision annealing in the mold, the stress of Example 1 is significantly reduced, and the stress value of the 20mm thick sample is reduced to below 50nm. In the comparative example, the refractive index of the sample obtained by purifying the raw materials in Comparative Example 1 by distillation method fluctuates greatly and is unstable; the number of periodic fluctuations in the radial stress distribution of Comparative Examples 2 and Comparative Examples 3 increases significantly. Within one cycle, the stress value is an accurate measurement value. After exceeding one cycle, it is shown that the density of periodic fluctuations represents the magnitude change trend of the relative central stress value, that is, the denser the fluctuations, the greater the stress value. From the analysis of the radial distribution of stress, the faster the fluctuations are to the edge, the greater the actual stress value; Comparative Example 4 after mold-free precision annealing has no periodic fluctuations, but the radial stress is quite different, and the maximum value is significantly higher than that of Example 1.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing large-sized and highly uniform infrared chalcogenide glass, characterized in that: The steps include: Step 1: purifying the raw materials by a low-temperature reduction method or a low-temperature solid fractionation method, mixing, and obtaining a purified mixture; the raw materials include at least two of Ge, As, Sb, Se, or Te; Step 2: Put the purified mixture into a quartz tube, vacuum dry it, seal the tube mouth with vacuum, and perform high-temperature swing melting at 750°C-900°C. After cooling to 300°C-600°C, place the quartz tube in a supercooled atmosphere and let it stand for solidification to obtain a glass precursor material. Step 3: heating the glass precursor material to 20°C-40°C below the glass transition temperature for the first annealing treatment, keeping the temperature, and removing the quartz tube outside the glass precursor material after cooling to room temperature to obtain a glass blank; Step 4: placing the glass blank in a mold for precision annealing treatment and slowly cooling to obtain a large-sized and highly uniform infrared chalcogenide glass; In step 4, the mold includes a ring, an upper cover plate and a lower base plate. When the ratio of the diameter of the glass blank to the thickness of the glass blank is ≥3, the thermal conductivity of the material used for the ring is 0.1Wm -1 K -1 -0.3Wm -1 K -1 When the ratio of the diameter of the glass blank to the thickness of the glass blank is less than 3, the thermal conductivity of the material used for the ring is 100Wm -1 K -1 -150Wm -1 K -1 The thermal conductivity of the material used for the upper cover plate and the lower base plate is 100Wm -1 K -1 -150Wm -1 K -1 .
2. The method for preparing large-size and highly uniform infrared chalcogenide glass according to claim 1, characterized in that: In step 1, the Ge single substance is purified by low temperature reduction method, the reduction temperature is 700°C-750°C, and the reduction time is 2h-4h; and / or In step 1, the As element is purified by low-temperature solid fractionation of As particles, the fractionation temperature is 200° C.-240° C., and the fractionation time is 1 h-3 h; and / or In step 1, the purity of each component in the purified mixture is ≥99.9999%.
3. The method for preparing large-size and highly uniform infrared chalcogenide glass according to claim 1, characterized in that: In step 2, the vacuum drying temperature is 65°C-85°C, the vacuum drying time is 60min-80min, and the vacuum degree of vacuum drying is less than 1×10 -3 Pa.
4. The method for preparing large-size and highly uniform infrared chalcogenide glass according to claim 1, characterized in that: In step 2, the specific operation of the high-temperature swing melting is: transfer the quartz tube with the tube mouth sealed to a swing furnace, heat it to 750℃-900℃ at a heating rate of 1℃ / min-4℃ / min, and then perform asymmetrical swing after constant temperature, and keep it warm for 8h-20h.
5. The method for preparing large-sized and highly uniform infrared chalcogenide glass according to claim 4, characterized in that: The tilt angle of the asymmetric swing is -40°-40°, and the swing frequency is 5 times / min-15 times / min.
6. The method for preparing large-sized and highly uniform infrared chalcogenide glass according to claim 1, characterized in that: In step 2, the temperature of the supercooled atmosphere is 60° C.-240° C.; and / or In step 2, the static curing time is 1h-3h.
7. The method for preparing large-size and highly uniform infrared chalcogenide glass according to claim 1, characterized in that: In step 3, the holding time of the first annealing treatment is 4h-6h; and / or In step three, the temperature is lowered to room temperature by programmed cooling at a rate of 0.2°C / min-0.5°C / min.
8. The method for preparing large-sized and highly uniform infrared chalcogenide glass according to claim 1, characterized in that: In step 4, the temperature of the precision annealing treatment is 170°C-400°C, and the holding time of the precision annealing treatment is 10h-50h; and / or In step 4, the temperature is slowly cooled by programmed cooling at a rate of 0.02°C / min-0.1°C / min; and / or In step 4, the distance between the edge of the mold and the edge of the glass blank is 2mm-5mm.
9. A large-size, highly uniform infrared chalcogenide glass, characterized in that: The glass is prepared by the method for preparing large-size and highly uniform infrared chalcogenide glass according to any one of claims 1 to 8.
10. Application of large-sized and highly uniform infrared chalcogenide glass in the preparation of infrared optical materials.
Citation Information
Patent Citations
Micro-structure hot pressing method for flat glass substrate for high-precision display
CN107793019A
Molding method for large-size chalcogenide glass and special large-caliber molding mold for large-size chalcogenide glass
CN110803861A
Method of obtaining intermediate products from fluoride glass
SU1740333A1
Curved Glass and Preparation Method Therefor, and Electronic Device
US20240294414A1
Cited By
Technological method for eliminating quartz glass stripes
CN121850335A
Process for eliminating striae in quartz glass
CN121850335B